KEPUTUSAN PETANI KAKAO BERALIH KE USAHATANI LADA DI KECAMATAN MARGATIGA KABUPATEN LAMPUNG TIMUR - Haq, Sofita Harfiatul; Prasmatiwi, Fembriarti Erry; Marlina, Lina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This study aims to analyze the income of cocoa farming and pepper farming, along with the factors that has influenced cocoa farmers to switch commodity from cocoa to pepper. The research location was chosen purposively in Sukadana Baru Village and Surya Mataram Village, Margatiga Sub-district, East Lampung Regency. Respondents involved in this study chosen by using random sampling technique, consisted of 32 cocoa farmers and 32 cocoa farmers who switched farming activity to do pepper farming. Data were collected from January to February 2023. The research methods used were income analysis method and logit method. The results show that cocoa farm income against total costs is IDR 2,055,595.08/ha and pepper farm income against total costs is IDR 13,292,748.37/ha, and the R/C values are more than one. R/C value of pepper farming is higher than cocoa farming; 2.30 for pepper farming and 1.16 for cocoa farming. In addition, factors that have a real effect on the decision of cocoa farmers to switch to pepper farming in Margatiga Subdistrict are age, experience and income. Keywords: cocoa, farm transfer, income, pepper